Penyelidikan Berat Jenis dan Daya Serap Untuk Agregat Halus - Samuel Breba Ginting (P3M- Politeknik Negeri Kupang, 2022)
Density of aggregate is the ratio between the solid mass of the aggregate and the mass of water with the same volume at the same temperature, while absorption is the ability of the aggregate to absorb water in dry to dry surface saturation conditions (SSD). This is what motivates the authors to compare and conclude the value of specific gravity and absorption of fine aggregates obtained with the standard. In this study, the authors discussed the investigation of density & absorption for fine aggregates properly and correctly and compared the density and absorption values ​​of fine aggregates obtained with the standard. Based on the specifications according to ASTM C-128,